STABILITY AND EVALUATION OF SOME CLIMATE-SMART SOYBEAN (Glycine max Linnaeus Merrill) GENOTYPES IN NIGERIA - Omonomo, P.; Gana, A.S.; Tolorunse, K.D.; Nwosu, D.J.; Shaahu, A.; Ajaye, O. F.; Adeyemo, B.D. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study evaluated the performance, stability, and adaptability of twenty soybean genotypes across five contrasting environments (Badeggi, Amakama, Numan, Yandev, and Makurdi) to identify climate-smart, high-yielding, and stable varieties suitable for large-scale production. The experiment was conducted using a Randomized Complete Block Design (RCBD) with three replications. Data were collected on plant height, pods per plant, pod clearance and seed yield. Results of the study showed highly significant (p ≤ 0.01) genotype, environment, and genotype × environment interaction (GEI) effects for most traits. The Additive Main Effects and Multiplicative Interaction (AMMI) analysis identified genotypes G12 (TGx_24_40NG-0088) and G16 (TGx_24_43NG-0126) as the highest-yielding, with large IPCA values. Genotypes G6 (TGx_24_9NG-0025), G7 (TGx_24_13NG-0031), G8 (TGx_24_15NG-0034), G9 (TGX_24_17NG-0039), and G18 (TGX 1904-6F) recorded low IPCA1 scores. The environments (Badeggi, Amakama, Yandev, and Makurdi) formed one mega-environment, while Numan emerged as a distinct second mega-environment. Overall, the study successfully identified both high-yielding and stable soybean genotypes suitable for Nigeria’s diverse Agro-ecologies. Genotypes G6 (TGx_24_9NG-0025), G7 (TGx_24_13NG-0031), G8 (TGx_24_15NG-0034), G9 (TGx_24_17NG-0039), and G18 (TGx 1904-6F) are recommended for wide adaptation, while G12 (TGx_24_40NG-0088) and G16 (TGx_24_43NG-0126) are ideal for high-potential environments. These findings provide essential information for soybean improvement, climate-smart agricultural planning, and national varietal release.